Goals are loves... an approach to program goals in peace. of security to integrity (an empty) (2014)
About twelve years ago, was created the program “all win playing fair”, which sought to promote processes of coexistence among growing numbers assistants barristas at Estadio Nemesio Camacho El Campin, to mitigate situations of violence generated by these groups. Presently, the “Goals for Peace” has positioned itself as a program capable to minimize such events at the Stadium. However, the phenomenon of the Barras it has been extended to the localities of Bogotá, generating dynamics of territorial appropriation by these groups that occasionally erupt in violence. Therefore, the program has a strong emphasis from the viewpoint of security, leaving aside key components to cover the phenomenon of Barras, such as Youth and Crisis of the value system, which can provide another perspective for intervention. This paper presents fragments of the investigation in 2012, the Goals in Peace program, in its 12 years. This aims to guide the reader about the phenomenon of the Barras from the experience of institutional program.